2019
DOI: 10.3889/oamjms.2019.469
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Nitroglycerin, N-Acetyl Cysteine and Metoprolol in CCL4 Induced Animal Model of Acute Liver Injury

Abstract: OBJECTIVE: The current study was designed to determine the hepatoprotective effect of well-known drugs. Nitroglycerin, N-acetyl cysteine and Metoprolol in acute liver injury induced by CCL4. The antioxidant effects of b-blockers, especially carvedilol, have been described by several investigators. However, for metoprolol, the effect is a bit query as there is only one in-vitro study showing a little hepatoprotective effect. Thus, it is worthy to re-study the hepatoprotective effect of metoprolol. AIM: To explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Acrolein was found to exert toxic action on the liver, affecting, among others, mitochondria of hepatocytes [89]. Al-Jawad et al [90] confirmed the hepatoprotective effect of N-acetylcysteine in a carbon tetrachloride (CCl 4 ) model of liver injury. Despite some reports about the hepatoprotection of carvedilol in other animal models of liver damage, such as CCl 4 -induced fibrosis [91] or I/R injury [92], our preliminary data did not confirm it, but a broader panel of studied parameters is necessary in order to make conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…Acrolein was found to exert toxic action on the liver, affecting, among others, mitochondria of hepatocytes [89]. Al-Jawad et al [90] confirmed the hepatoprotective effect of N-acetylcysteine in a carbon tetrachloride (CCl 4 ) model of liver injury. Despite some reports about the hepatoprotection of carvedilol in other animal models of liver damage, such as CCl 4 -induced fibrosis [91] or I/R injury [92], our preliminary data did not confirm it, but a broader panel of studied parameters is necessary in order to make conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…This leads to a deficiency of coenzymes and the resulting increase in toxic substances that cause many adverse side effects. As a consequence, 1-5 mg folic acid is prescribed as a treatment to avoid malnutrition as well as MTX-related side effects involving mouth ulcers and gastrointestinal discomfort [19], [20]. In the absence of elevated consumption, malignancy is a catabolic condition synonymous with lower serum folate rates [21], [22].…”
Section: Discussionmentioning
confidence: 99%
“…NO, along with the radicals such as the superoxide anions could generate oxidants that are known to be less toxic [ 20 , 21 ]. Few published studies suggest that NO production endogenously or its administration exogenously could reduce the hepatic toxicity induced by the oxidants [ 3 , 22 , 23 , 24 , 25 ] while endogenous NO production inhibition has potentiated cellular damage [ 26 , 27 ]. In addition, many studies have suggested that NO is required for the daily operations of the body.…”
Section: Introductionmentioning
confidence: 99%